Petrology of permian coal, Vasse Shelf, Perth Basin, Western Australia - Santoso, Binarko (Curtin University, 1994)
The Early Permian coal samples for the study were obtained from the Vasse Shelf, southern Perth Basin, located approximately 200 km south- west of Perth. The selected coal samples for the study were also obtained from the Premier Sub-basin of the Collie Basin and the Irwin Sub-basin of the Perth Basin. The Early Permian coal measures are described as the Sue Coal Measures from the Vasse Shelf, the Ewington Coal Measures from the Premier Sub-basin and the coal measures from the Irwin sub-basin are described as the Irwin River Coal Measures.The Vasse Shelf coal is finely banded and the dominant lithotypes are dull and dull banded types, followed by bright banded and banded types, with minor bright types. The variation of dull and bright lithotypes represents fluctuating conditions of water table level during the growth of peat in the swamp. The maceral composition of the coal is predominantly composed of inertinite, followed by vitrinite and minor exinite and mineral matter. The coal is characterized by very low to medium semifusinite ratio and medium to high vitrinite content, supporting the deposition in anaerobic wet conditions with some degree of oxidation. The coal is classified as sub- bituminous to high volatile bituminous of the Australian classification. In terms of microlithotype group, the predominance of inertite over vitrite suggests the coal was formed under drier conditions with high degree of oxidation during its deposition. On the basis of the interpretations of lithotypes, macerals, microlithotypes and trace elements, the depositional environment of the coal is braided and meandering deltaic-river system without any brackish or marine influence.The maceral composition of the Collie coal predominantly consists of inertinite and vitrinite, with low exinite and mineral matter. The very low to low semifusinite ratio and low to medium vitrinite content of the coal indicate that the coal was formed under aerobic dry to wet conditions with some degree of oxidation. The coal is categorized as sub-bituminous according to the Australian classification. The domination of inertite and durite over vitrite and clarite contents in the coal reflects the deposition under drier conditions with fluctuations in the water table. On the basis of the interpretations of macerals, microlithotypes and trace elements distribution, the depositional environment of the coal is lacustrine, braided to meandering fluvial system, without the influence of any marine influx.The maceral composition of the Irwin River coal consists predominantly of vitrinite and inertinite, and minor exinite and mineral matter. The coal has very low semifusinite ratio and medium to high vitrinite content, suggesting the coal was deposited in anaerobic wet conditions with some degree of oxidation. The coal is classified as sub-bituminous of the Australian classification. The predominance of vitrite and clarite over inertite and durite contents in the coal indicates that the coal was formed in wetter conditions and in high water covers with a low degree of oxidation. Based on macerals and microlithotypes contents, the depositional environment of the coal is braided fluvial to deltaic, which is in accordance with the interpreted non- marine and mixed marine environment of deposition in the sub-basin.The petrological comparisons of Vasse Shelf, Collie and Irwin River coals show that the average vitrinite content of the Irwin River coal is highest (49.1%) and of the Collie coal is lowest (37.3%) of the three. The inertinite content is highest in Collie coal (49.1%), followed by Vasse Shelf (46.4%) and Irwin River (39.2%) coals. The exinite content is low in Irwin River coal (6.3%) as compared with Vasse Shelf (9.0°/,) and Collie (8.3%) coals. The mineral matter content is relatively low for all the three coals. The rank of the Vasse Shelf coal is high as compared with the Collie and Irwin River coals, either due to tectonic uplift after the deposition in post-Permian in the southern Perth Basin, or due to the average depth of burial over Vasse Shelf which is much greater than that of Collie and Irwin River coals.The comparisons of the coal from Western Australia with the selected Gondwana coals show that the predominance of inertinite over vitrinite occurs in the Western Australian coals (Vasse Shelf and Collie Basin). On the other hand, the Brazilian, eastern Australian, Indian and Western Australian (Irwin Sub-basin) coals are dominated by vitrinite over inertinite. The exinite content is highest in the Indian coals and lowest in the eastern Australian coals. The mineral matter content is highest in the Brazilian and Indian coals, and lowest in Western Australian (Vasse Shelf) and eastern Australian (Sydney Basin) coals. The rank of the coals ranges from sub- bituminous to medium volatile bituminous according to the Australian classification.